A review of the main determinants of capital structure of smaller firms and an empirical investigation on a sample of small Italian firms - Domenichelli, Oscar (Piccola Impresa / Small Business, 2012)
This paper aimed to empirically test the influence of major determinants of capital structure of the small firms of the Marche Region (Italy) on the debt-to-equity ratio. On the whole, the research clearly shows the importance of the pecking order theory; does not suggest the presence of agency costs of debt; and does not indicate a strong support for the trade-off theory, even if the signs of the relationships between effective tax rate, non-debt tax shields and default risk, on the one hand, and debt-to-equity ratio, on the other, together with the importance of the tax burden and non-debt tax shields of the firms observed would not exclude their convergence towards a long-term optimal debt level, to trade-off the costs of financial distress against the tax benefits associated with debt financing. The comparative empirical analysis also highlights that, on the whole, the same determinants have similar effects, in terms of signs, on the capital structure of the manufacturing and trade firms, even if, in this latter case, none of the relationships being considered is statistically significant.